Early onset sebaceous carcinoma - Kaltreider Sara A; Sung Dongjin; Gonzalez-Fernandez Federico (BMC, 2011)
Abstract Background Ocular sebaceous carcinoma can masquerade as benign lesions resulting in delay of diagnosis. Early recognition is even more difficult in young patients where the disease rarely occurs. Here, we provide a clinicopathological correlation of ocular sebaceous carcinoma in a young individual lacking history of hereditary cancer or immunosuppression. Findings A detailed histopathological study including p53 DNA sequencing was performed on an aggressive sebaceous carcinoma presenting in a healthy 32 year-old Caucasian woman. She had no history of retinoblastoma, evidence for a hereditary cancer syndrome, or radiation therapy. However, she potentially was at risk for excessive UV light exposure. A detailed review of the literature is also provided. A moderately well differentiated sebaceous carcinoma was established histopathologically arising from the meibomian gland of the upper eyelid. In most areas, the cytoplasm contained small but distinct Oil-red-O positive vacuoles. Direct sequencing of p53 identified a G:C→A:T mutation at a dipyrimidine site. The mutation results in substitution of arginine for the highly conserved glycine at residue 199 located at the p53 dimer-dimer interface. Energy minimization structural modeling predicts that G199R will neutralize negative charges contributed by nearby inter- and intramonomeric glutamate residues. Discussion This study points to the importance of recognizing that sebaceous carcinoma can occur in young patients with no evidence for hereditary cancer risk or radiation therapy. The G199R substitution is anticipated to alter the stability of the p53 tetrameric complex. The role of UV light in the etiology of sebaceous carcinoma deserves further study. Our findings, taken together with those of others, suggest that different environmental factors could lead to the development of sebaceous carcinoma in different patients.